Do polygynous males of Akodon azarae (Rodentia: Sigmodontinae) vary their mating tactics at low availability of females? - Bonatto, Maria Florencia (2015)
We examined in Akodon azarae if at low availability of females (sex ratio biased toward males, 3:1), the mating tactics of males are determined by the number of receptive females to which they have access, or by the number of male competitors with which they interact. To test these hypotheses, we measured the home range size and overlap degree. At the beginning of the reproductive season, we studied spacing patterns using 57 and 30 home ranges established by reproductive males and females in three enclosure populations. We statistically compared our results with those previously obtained in enclosure populations with a sex ratio of 1:1. Male home range sizes were larger than those recorded in populations with a sex ratio of 1:1. The degree of male intra-sexual overlap increased about 3.5 times with respect to that observed under a sex ratio of 1:1. The increase in home range sizes and intra-sexual overlap degree of reproductive males reflects that A. azarae males may adjust their spacing strategy to increase their mating opportunities at low density of females. Our results suggest that at low breeding female availability, male mating tactics could be determined by the number of receptive females to which they have access.